Experimental Investigation and Molecular Dynamics Modeling of the Effects of K2O on the Structure and Viscosity of SiO2-CaO-Al2O3-MgO-K2O Slags at High Temperatures - Fan Yang; Qingguo Xue; Haibin Zuo; Yu Liu; Jingsong Wang (Metals, 2025)
Variations in slag properties critically influence smelting operations and product quality. The effects of K2O on the CaO-SiO2-MgO-Al2O3-K2O slag system at 1823 K were systematically analyzed through an integrated approach combining viscosity measurements, FTIR spectroscopy, and molecular dynamics simulations. The results revealed a rapid 52% decrease in slag viscosity and an 18.32 kJ/mol reduction in activation energy as K2O content increased from 0% to 3%. K2O releases O2− ions that depolymerize Si-O network structures. Within the 3% to 5% range, structural network formation is promoted by the K2O-SiO2 reaction, resulting in increased slag viscosity and elevated activation energy. Molecular dynamics simulations elucidate the depolymerization of complex Si-O networks, accompanied by a proliferation of smaller [AlO4] tetrahedral fragments. The diminished Si-O-Si bridging oxygen (BO) bonds contrast with the enhanced increase in Si-O-K non-bridging oxygen (NBO) linkages. When K2O exceeds 3%, the diffusion capacity of K atoms becomes constrained as K2O participates in structural network assembly, a phenomenon validated by FTIR spectroscopic analysis. Elevated K2O concentrations enhance slag network polymerization, leading to increased viscosity. Therefore, the precise control of K2O content is critical during smelting operations and by-product manufacturing (e.g., glass or mineral wool) to optimize material performance. These findings provide theoretical support for controlling the alkali metal content during the actual metallurgical process and thus further optimizing blast furnace operation.